Digital Competence in Cybercrime Behaviours: A Study Based on Eurobarometer Research - Gruchoła, Małgorzata; Szulich-Kałuża, Justyna (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2022)
The purpose of the article is a study of components of digital competence (technological and humanistic) in cybercrime behaviours, based on the example of internet levels (technical, social and informative) as well as the confrontation of theoretical assumptions with the frequency of their experience by the citizens of the European Union. Subject to analysis were fourteen reports of Eurobarometer, carried out in twenty-eight countries of the EU in the years 2011-2019. The method applied is a quantitative and qualitative analysis of data available, comparative, historical as well as analytical-synthetic. Two research hypotheses were accepted: 1) A catalogue formulation of digital competences focusing on social-demographic traits should be replaced by a relational formulation taking into account the skills, knowledge and attitude of internet users. 2) EU citizens possess greater digital competences of a technological character and more often admit being affected by cybercrime behaviours of a technological kind than of a humanistic one. The first hypothesis was confirmed, whereas the second was only partially confirmed. In basing ourselves on a typology of three layers of the internet, we proposed two areas of digital competence: technological competence and humanistic competence (social and informative). These were subordinated to particular layers of the internet and in this context an analysis was carried out of the social opinion of EU citizens on the subject of cybercrime behaviours. The low level of humanistic competence (52%) reported by EU citizens determines a high degree of fear which does not show a causal-effective connection in the actual level of noted experiences of being a victim of criminal behaviour.